Aspartokinase of Streptococcus mutans: purification, properties, and regulation. - McCarron, R M (1978)
Aspartokinase from Streptococcus mutans BHT was purified to homogeneity and characterized. The molecular weight of the native enzyme was estimated to be 242,000 by gel filtration. Cross-linking of aspartokinase with dimethyl suberimidate and polyacrylamide gel electrophoresis of the amidinated enzyme in the presence of sodium dodecyl sulfate showed the enzyme to be composed of six identical subunits with a molecular wieght of 40,000. The optimal pH range for enzyme activity was 6.5 to 8.5. The apparent Michaelis-Menten constants for aspartate and ATP were 5.5 and 2.2 mM, respectively. The enzyme was stable within the temperature range of 10 to 35 degrees C. Aspartokinase was not feedback inhibited by individual amino acids, but was concertedly inhibited by L-lysine and L-threonine (93.5% inhibition at 10 mM each). The inhibition was noncompetitive with respect to aspartate (Ki = 10 mM) and mixed with respect to ATP. L-Threonine methyl ester and L-threonine amide were able to substitute for L-threonine in feedback inhibition, but the requirement for L-lysine uas strict. The feedback inhibitor pair protected the enzyme against heat denaturation. Aspartokinase synthesis was repressed by L-threonine; this repression was enhanced by L-lysine, but was slightly attenuated by L-methionine.